1995
DOI: 10.1523/jneurosci.15-12-08083.1995
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale reorganization at multiple levels of the somatosensory pathway follows therapeutic amputation of the hand in monkeys

Abstract: Reorganization of somatosensory cortex after peripheral nerve damage typically has been attributed to cortical plasticity. Here we provide evidence that much of the large-scale cortical reorganization that occurs after a major loss of peripheral inputs reflects the sprouting or expansion of afferents from the remaining forelimb into deprived territories of the spinal cord and brainstem. We examined sensory afferent terminations in the spinal cord and brainstem, and determined the somatotopic organization of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
178
1
10

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(203 citation statements)
references
References 68 publications
14
178
1
10
Order By: Relevance
“…In addition, the clinical samples used in previous research might be very different from our self-selected amputee sample. Our data indicate that the loss of input from a limb in the pre-or early postnatal stage does not lead to significant reorganizational changes in SI (as one might deduce from animal studies; see Merzenich et al 1984;Pons et al 1991;Florence and Kaas 1995)]. …”
Section: Cortical Reorganization and Sensory Perception In Congenitalsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, the clinical samples used in previous research might be very different from our self-selected amputee sample. Our data indicate that the loss of input from a limb in the pre-or early postnatal stage does not lead to significant reorganizational changes in SI (as one might deduce from animal studies; see Merzenich et al 1984;Pons et al 1991;Florence and Kaas 1995)]. …”
Section: Cortical Reorganization and Sensory Perception In Congenitalsupporting
confidence: 54%
“…Although we have thus far addressed only the functional reorganization in SI after amputation, it is quite possible that the original locus of these alterations is not in somatosensory cortex but is rather at the level of the spinal cord or the thalamus (Howe 1983;Florence and Kaas 1995;Jain et al 1997). Furthermore, the role of interhemispheric transfer requires investigation.…”
Section: Cortical Reorganization and Sensory Perception In Congenitalmentioning
confidence: 99%
“…Previous experiments in animals have shown that reorganization can occur at the cortical level following peripheral injury (Pons et al, 1988(Pons et al, ,1991Guilbaud et al, 1991Guilbaud et al, ,1992Recanzone et al, 1992;Mao et al, 1993;Florence and Kaas, 1995;Chen et al, 1998). Guilbaud et al (1991) described abnormal spontaneous 'paroxysmal' discharges in S1 neurons that occurred without stimulation and which lasted up to 5 minutes in CCI animals.…”
Section: Forebrain Activation Pattern During Spontaneous Chronic Painmentioning
confidence: 98%
“…Cortical plasticity has also been reported in humans with referred phantom sensations after spinal cord injury (Mackert et al, 2003;Moore et al, 2000). While some of these effects may be attributed to changes in subcortical somatosensory pathways and reflection of these changes in the somatosensory cortex (Florence and Kaas, 1995;Kaas, 2002;Wall et al, 2002), several lines of evidence indicate that alterations in intracortical pathways play a major role in functional plasticity. Interestingly, different forms of cortical plasticity are manifested during early stages of cortical development and throughout maturity.…”
mentioning
confidence: 97%